An Archetypal Phenomenology of Skholé. Issue 3 (29th December 2017) - Kennedy, David
Abstract: In this essay David Kennedy argues that children represent one vanguard of an emergent shift in Western subjectivity, and that adult–child dialogue, especially in the context of schooling, is a key locus for the epistemological change that implies. Following Herbert Marcuse's invocation of a "new sensibility, " Kennedy argues that the evolutionary phenomenon of neoteny — the long formative period of human childhood and the paedomorphic character of humans across the life cycle — makes of the adult–child collective of school a primary site for the reconstruction of belief. After exploring child–adult dialogue more broadly as a form of dialectical interaction between what John Dewey called "impulse" and "habit, " Kennedy identifies three key dimensions of dialogic schooling, all of which are grounded in a fourth: the form of dialogical group discourse called community of philosophical inquiry (CPI), which is based on the problematization and reconstruction of concepts through critical argumentation. As a discourse model, CPI grounds practice in all of the dialogic school's emergent curricular spaces, whether science or mathematics, whether literature, art, or philosophy. Second, CPI opens a functional space for shared decision making and collaborative governance, making of school an exemplary model of direct democracy. Finally, CPI as a site for the critical interrogation of concepts encountered in the curriculum (such as "alive, " "justice, " "system, " and "biosphere") and as a site for democratic governance leads naturally to expression in activist projects that model an emergent "new reality principle" through concrete solutions to practical problems on local and global levels.